RANCANG BANGUN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN METODE DEMONSTRASI UNTUK KELAS 1 SEKOLAH DASAR - Muhammad Arif Julyananda; Tien Yulianti; Donaya Pasha (Universitas Teknokrat Indonesia, 2022)
During this primary school mathematics learning method is conventional, namely the teacher notes the material on the blackboard and gives lectures. This causes students to be less efficient in understanding the mathematics subject matter delivered because of the lack of visualization in mathematics. So that mathematics learning media is needed to help students in learning. This study aims to build a mathematics learning media for grade 1 elementary school. Methods of data collection using interviews, documentation, and literature study. Mathematics learning media for grade 1 SD is built with Contruct 2 and CorelDraw Graphics Suite X7. The application development phase includes analysis, system design, implementation, and testing. Mathematics learning media applications for grade 1 elementary school can be used as media by teachers and students in giving and receiving mathematics learning materials, so that it can make it easier for students to understand the material and make it easier to understand the material. teacher to deliver the material. The system test results show that this application is feasible and can be used as a learning aid for mathematics in grade 1 elementary school.